Performance, asymmetry and biomechanical parameters in wheelchair rugby players - Bakatchina, S.; Weissland, T.; Astier, M.; Pradon, D.; Faupin, A. (Sports Biomechanics, 2024)
The practice of the wheelchair rugby is becoming more and more worldwide. However, few biomechanical studies have focused on this sport. The aim of this study was to compare kinematic parameters of wheelchair rugby players, classified as defensive players (LP-D) versus offensive players (HP-O). Twenty-nine wheelchair rugby players (17 LP-D and 12 HP-O) performed a 20-m sprint test. The peak velocities, temporal parameters (propulsion phase time, deceleration phase time, cycle time and cycle frequencies) and asymmetries (the difference in peak velocities between the right and the left wheels) were measured at the acceleration and constant peak velocity phases of the sprint by an inertial measurement unit which was placed on each rear wheel. At the acceleration and constant peak velocity phases, peak velocities and cycle frequencies were higher in HP-O players than LP-D players. The deceleration phase times and the cycle times were higher in LP-D players than HP-O players. However, no significant difference in asymmetry was found between LP-D players and HP-O players. The HP-O players showed superior performance than the LP-D players, but they could be more exposed at risk of injury at their upper limbs than LP-D players.